The Analysis of 21st Century Learning Implementation and Competency Achievement of Junior High School Students in 3T Regions - Gunadi, Gunadi; Haryono, Haryono; Purwanti, Eko (Innovative Journal of Curriculum and Educational Technology, 2022)
Providing students with competency is one of the challenge of 21st Century learning. The competencies include critical thinking and problem solving skills, communication and collaboration, creativity and innovation, as well as information literacy and technology media. This study aims to analyze the implementation of 21st century learning and the achievement of competencies of junior high school students who are in the frontier, outermost, and least developed areas of Melawi Regency, West Kalimantan Province. The method of this study was descriptive-analytic qualitative with the type of the research was case study. The results shows that the implementation of 21st century learning at Junior High School in the 3T area shows a moderate or medium category. The scores for each indicator are: planning (70.4%), learning implementation (73.4%), and assessment and evaluation (70.8%). The achievement of the 21st century competence of students gets medium category. The scores for each indicator are: critical thinking and problem solving skills (54%), communication skills (73%), collaboration skills (70%), creativity and innovation (48%), and information and media literacy (60%). The implication of this research is for the prospective teachers or new teachers who work in the 3T area. So that, they would know the conditions and prepare various strategies and learning approaches to apply based on the local conditions in improving students’ competency.